2001
DOI: 10.1302/0301-620x.83b6.0830921
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proximal femoral strain after insertion of uncemented standard and customised femoral stems

Abstract: We have compared the changes in the pattern of the principal strains in the proximal femur after insertion of eight uncemented anatomical stems and eight customised stems in human cadaver femora. During testing we aimed to reproduce the physiological loads on the proximal femur and to simulate single-leg stance and stair-climbing.The strains in the intact femora were measured and there were no significant differences in principal tensile and compressive strains in the left and right femora of each pair. The tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
(32 reference statements)
4
30
0
1
Order By: Relevance
“…Our laboratory has traditionally used fresh frozen femurs for biomechanical experiments (Aamodt et al 2001, Wik et al 2010) and fresh frozen femurs were chosen accordingly. During the course of our study embalmed femurs were shown to provide similar mechanical properties to fresh frozen ones and could have been an alternative (Topp et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has traditionally used fresh frozen femurs for biomechanical experiments (Aamodt et al 2001, Wik et al 2010) and fresh frozen femurs were chosen accordingly. During the course of our study embalmed femurs were shown to provide similar mechanical properties to fresh frozen ones and could have been an alternative (Topp et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible to apply torque in constrained femurs (Brandt et al 2006), more degrees of freedom in the hip-jig make a separate application of torque possible. The torque can then be applied to the femoral head (Deneka et al 1997) or the distal diaphysis (Aamodt et al 2001).…”
Section: Test Setupsmentioning
confidence: 99%
“…Femoral components that engage the metaphysis and load the femur both medially and laterally are inherently more stable [1,4,12]. The stem does not need to be 'press-fitted' into the femur or driven distally (interference fit) in the diaphysis to achieve initial stability.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of the Unique stem are in agreement with this. Thus, the 2 year bone remodeling around the custom-made stem does not seem to reflect the retention of the postoperative cortical strains that has been demonstrated experimentally [3]. Two studies of stems with reduced stiffness have shown either a reduced loss in BMD or a gain of BMD [8,18].…”
Section: Bone-mineral Densitymentioning
confidence: 99%